2021
DOI: 10.3390/nu13020368
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplements and Risk of Cardiovascular Disease: A Meta-Analysis of Clinical Trials

Abstract: Background: Recent systematic reviews and meta-analyses of randomized, double-blind, placebo-controlled trials (double-blind, placebo-controlled RCTs) have reported controversial findings regarding the associations between calcium supplements on the risk of cardiovascular disease (CVD). This meta-analysis aimed to investigate the association between them. Methods: We searched PubMed, EMBASE, the Cochrane Library, and the bibliographies of relevant articles for double-blind, placebo-controlled RCTs in November,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 41 publications
1
29
0
3
Order By: Relevance
“…Furthermore, Michaëlsson et al found that a high calcium intake is related to high all-cause mortality [19]. Our findings are consistent with those of previous studies which showed that calcium supplementation is associated with an increased risk of myocardial infarction [7,10,17], ischemic stroke [8], and death [19] in other populations. Moreover, our findings suggest that calcium supplementation may increase the risk of myocardial infarction and ischemic stroke in Koreans, who are known to have little calcium intake.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Michaëlsson et al found that a high calcium intake is related to high all-cause mortality [19]. Our findings are consistent with those of previous studies which showed that calcium supplementation is associated with an increased risk of myocardial infarction [7,10,17], ischemic stroke [8], and death [19] in other populations. Moreover, our findings suggest that calcium supplementation may increase the risk of myocardial infarction and ischemic stroke in Koreans, who are known to have little calcium intake.…”
Section: Discussionsupporting
confidence: 92%
“…While two previous meta-analyses by Bolland et al [7,17] reported an association between calcium supplementation and the risk of myocardial infarction, two other meta-analyses by Chung et al [18] and Lewis et al [9] showed no relationship between calcium supplementation and cardiovascular disease risk. However, a recent meta-analysis by Myung et al showed that calcium supplementation increased the risk of coronary heart disease [10]. Abajo et al suggested that calcium supplementation might increase the risk of ischemic stroke [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, calcium supplementation can be beneficial for bone health in children, older adults, and postmenopausal women [ 3 ]. However, there is also increasing concern regarding the possible link between serum calcium levels and cardiovascular events [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…High calcium waters may be a calorie-free nutritional supplement for those with low calcium levels as calcium supplements were thought to increase cardiovascular (CVD) risk [29,30]. However, although the relationship between calcium intake and bone formation is clear, controversy remains whether calcium intake affects the risk for CVD as the evidence is contradictory [31][32][33].…”
Section: Discussionmentioning
confidence: 99%